Bone histology, phylogeny, and palaeognathous birds (Aves: Palaeognathae). (August 2014) - Legendre, Lucas J.; Bourdon, Estelle; Scofield, R. Paul; Tennyson, Alan J. D.; Lamrous, Hayat; de Ricqlès, Armand; Cubo, Jorge
<x xml:space="preserve">Abstract</x> The presence of a phylogenetic signal in the variation of osteohistological features has been recently debated in the literature. Previous studies have found a significant signal for some features, but these results were obtained on a small amount of characters and a reduced sample. Here we perform a comprehensive study in which we quantify the phylogenetic signal on 62 osteohistological features in an exhaustive sample of palaeognathous birds. We used four different estimators to measure phylogenetic signal – Pagel's λ, Abouheif's Cmean, Blomberg's K, and Diniz‐Filho's phylogenetic eigenvector regressions PVR – and four topologies taken from the literature. Bone size and bone vascular density exhibit a strong phylogenetic signal, whereas all but four of the remaining features measured at the histological level – cellular size in caudal and medial transects of femora, and proportion of oblique vascular canals in rostral and caudal transects of tibiotarsi – exhibit a weaker signal. We also found that the impact of the topologies used in the analyses is very low compared with that of sample size. We conclude that the analysis of a comprehensive sample is crucial to obtain reliable quantifications of the phylogenetic signal. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 112, 688–700.